ANALISIS KINERJA KEUANGAN BLUD PUSKESMAS KABUPATEN KARANGANYAR TAHUN 2020-2022 - Jannah, Miftahul; Adib Alfathin, Muhammad; Tri H, Santoso (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to determine the financial performance of BLUD Puskesmas in Karanganyar Regency based on liquidity, efficiency, effectiveness and level of independence of BLUD in accordance with the Regulation of the Director General of State Treasury of the Ministry of Finance of the Republic of Indonesia Number PER-11/PB/2021. This type of research is qualitative research with a descriptive-qualitative approach method. Data collection techniques using literature studies and documentation of the financial statements of BLUD Puskesmas in Karanganyar Regency for 2020-2022. The results showed that BLUD Puskesmas in Karanganyar Regency did not yet have regulations on BLUD governance and performance assessment (maturity level), the financial performance of BLUD Puskesmas in Karanganyar Regency in 2020-2022 was included in the very liquid criteria with a percentage of 6697%, the efficiency of BLUD Puskesmas in Karanganyar Regency in 2020-2022 received inefficient criteria with a percentage of 100%, the effectiveness of BLUD Puskesmas in Karanganyar Regency in 2020-2022 is ineffective with a percentage of 2%, and the level of independence of BLUD Puskesmas in Karanganyar Regency is relatively low with a consultative relationship pattern with a percentage value of 37%.